ANALISIS SURVEY FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAK PIDANA KORUPSI APARAT PEMERINTAH DAERAH DAN PENCEGAHANNYA DI PROVINSI JAWA TENGAH - Chrisna Suhendi; Zaenuddin Zaenuddin (Jurnal Akuntansi Indonesia, 2015)
This study aims to identify the effectiveness and efficiency of the implementation of good governance based on information technology (e-Governance) in the Central Java provincial government. It is intended that the corruption done by government officials could be prevented/avoided. To achieve this goal it is necessary to identify the existing conditions and constraints that arise both from internal and external factors that may impede the implementation of this system. The population in this study is all whole Unit of SKPD in Central Java Provincial Government with the unit of analysis the Head of SKPD. In this study, the samples are taken by using proportional random sampling. The results of discussion on the study of corruption and e-governance conclude that the types of state capture , influence and administrative corruption can happen anytime and anywhere. Yet, the biggest concern of the corruption by government officials is administrative corruption. To prevent the corruption of local governments, it should implement the use of e-governance or the application of information technology to support the implementation of good-governance systems. However, the most important thing is the commitment of all officials in local government.